ANALISIS PENGARUH KREATIFITAS IKLAN DAN KREDIBILITAS ENDORSER TERHADAP EFEKTIFITAS IKLAN SERTA IMPLIKASINYA PADA SIKAP TERHADAP MEREK (Studi Pada Iklan Televisi PT Djarum Di Kota Semarang) - Wulandari, Wulandari (Master of Management Diponegoro University, 2009)
The 2008 Survey of SWA and MARS show that Top of Mind (TOM) Advertising of Djarum cigarette is 12.7 and the TOM Brand is 11.9. While in the 2007 survey show that TOM Brand of Djarum is 13.1 and it is higher that the TOM Advertising which is 12.1. This shows that there is a decline in TOM Brand from 13.1 in 2007 to be 11.9 in 2008. And there is an insignificant increase in TOM Advertising approximately 0.6 from 12.1 in 2007 to 12.7 in 2008. It is suspected that this is the cause of uncreative advertising of the Djarum cigarrete so that the advertising becomes ineffective. Hence, the problem of this research is How to improve the advertising effectiveness through the advertising creativity and the endorser credibility impacting the attitude toward the ad?To answer the problem of this research, questionnaires is distributed to 140 respondents. The respondent are people who had seen the advertising of Djarum. The questionnaire consist of items about the advertising creativity, endorser credibility, advertising effectiveness and the attitude toward the ad. Then, the data is being analyzed with Structural Equation Modeling (SEM) Analysis Method.The results of the SEM analysis method show that the hypotheses which say that the more creative an advertising is, the higher the advertising effectiveness; the higher the credibility of the endorser, the more effective the advertising is and that the more effective the advertising, the more positive the attitude toward the ad is, had proven to be statistically accepted.